2011
DOI: 10.1158/1541-7786.mcr-11-0185
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IRF4 by IRF1, 3, and 7 in Noxa Expression Is a Necessary Event for IFN-γ–Mediated Tumor Elimination

Abstract: IFN-g plays a critical role in tumor immunosurveillance by affecting either immune cells or tumor cells; however, IFN-mediated effects on tumor elimination are largely unknown. In this study, we showed that IFN regulatory factors (IRF) modulated by IFNs up-and downregulated Noxa expression, a prodeath BH3 protein, in various cancer cells. Inhibition of Noxa expression using short hairpin RNA in tumor cells leads to resistance against lipopolysaccharide (LPS)-induced tumor elimination, in which IFN-g is known a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Indeed, EZH2i treatment of ARD but not ARP-1 cells induced the expression of BCL6, IRF1 and BATF transcription factors (Fig. 5E, 6F-G), all reported to repress IRF4 expression (Ci et al, 2009, Piya et al, 2011, Kurachi et al, 2014). To ascertain the underlying cause of BCL6 exclusive activation in UTX -null cells upon treatment with EZH2i, we performed ChIP for H3K27me3 and H3K27ac in ARD and ARP-1 cells.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, EZH2i treatment of ARD but not ARP-1 cells induced the expression of BCL6, IRF1 and BATF transcription factors (Fig. 5E, 6F-G), all reported to repress IRF4 expression (Ci et al, 2009, Piya et al, 2011, Kurachi et al, 2014). To ascertain the underlying cause of BCL6 exclusive activation in UTX -null cells upon treatment with EZH2i, we performed ChIP for H3K27me3 and H3K27ac in ARD and ARP-1 cells.…”
Section: Resultsmentioning
confidence: 91%
“…IRF3 expression has been shown to be induced by IFNγ and be neuroprotective in the CNS (Koziczak-Holbro et al, 2008; Piya et al, 2011; Tarassishin et al, 2011). IRF7 is also crucial to the interferon response (Honda et al, 2005b; Nakajima et al, 2009; Ning et al, 2011) and upregulation of IRF7 in vivo has been shown to play a protective role in the CNS (Honda and Taniguchi, 2006; Salem et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, IRF-1 can bind to the same regulatory sites as Blimp-1 (34); however, the relevance of this observation has not been tested in vivo. IRF-1 opposes IRF-4-mediated gene regulation in cancer and mouse kidney cells (35); however, it is not clear whether this also happens during B cell differentiation. In this study, we observed a slight but statistically significant increase in the germinal center B cell population in naive IRF-1 Ϫ/Ϫ mouse spleens.…”
Section: Discussionmentioning
confidence: 99%